Socio-constructivist pedagogy in physical and virtual spaces: the impacts and opportunities on dialogic learning in creative disciplines. (11th May 2022) - Smith, Charlie
Abstract : The process and outcomes of the design studio are extensively communicated through visual means. However, notwithstanding such tangible manifestations of learning, design education is characterised by dialogue, the discussions in studio between tutors and students and between the students themselves. As such, it aligns strongly with socio-constructivism, where learning is co-constructed and negotiated through a social process of collaborative dialogue. This article evaluates the impact of the transition from studio-based encounters to virtual learning on a pedagogy that revolves around dialogic interaction, the dynamics of which arguably become distinctly different online. Utilising a combination of reflecting on teaching practices and research literature, this article explores the effects of a variety of signature elements on architectural pedagogy through which dialogic learning occurs, such as one-to-one tutorials (desk crits), group tutorials and design reviews (crits or juries). Socio-constructivism suggests that dialogue and co-construction are key processes for learning; the question is: was this effectively replicated in a virtual format? Post-lockdown, some institutions are retaining elements of virtual teaching alongside face-to-face through a blended learning approach. The article considers the implications of this for creative disciplines. In the return to face-to-face teaching after the prolonged hiatus created by the pandemic, some students have very little experience of studio culture; the article discusses the potential consequences and opportunities that this presents. Learning from the experiences of remote teaching during the pandemic, the article concludes by suggesting qualities that might be embedded within both physical and virtual creative learning spaces to facilitate more compassionate and engaging dialogic learning.